OPTIMALISASI MANAJEMEN JARINGAN DENGAN MENGGUNAKAN Mikrotik RouterOS - Minda Mora Purba; Syamsu H (Fakultas Ilmu Komputer dan Desain - Unsurya, 2015)
Computer networks ( Computer Network ) is a network of data communication system that involves one or more computer systems are connected by transmission lines to form a system of communication tools . With the network , one computer can use the data on another computer , the printer can print a report on another computer , the computer can give the news to others although different areas . Network is the concept of network data communication systems . Network may involve only a single computer system with multiple terminals in different locations or involve multiple computer systems at different locations .For a company that is engaged in the management of care of all the needs of companies that are still in the group , the company requires Internet technology for the company's business activities , either between departments or branches are located in several parts of Indonesia . Therefore, the company is very necessary to support the good performance networking technologies . If the network management is not going well , it is causing some problems in running the daily operations .